Os arranjos produtivos locais e seus reflexos na família de micro e pequenos confeccionistas de Ubá/MG e microrregião - Teixeira, Débora Pires (2009)
The local productive arrangements (LPA) became one of the main policies local and regional development in Brazil, due to their ability to create processes of evolution of society, and result in economic and social development, inclusion and better life quality of the involved people. This study aimed to analyze the impact of LPA clothing from Ubá microregion on the studied businessmen families. This research consisted of two phases: in the first one the LPA foundation process was characterized, with the evaluation of the first three years of the arrangement operation (2005-2007). LPA managers were interviewed, a sample of 20 clothing workers, which was divided into two groups according to the degree of participation in the arrangement actions (attendance): group A, with a high degree of participation and involvement with LPA; and group B (control), with low degree of participation and involvement with LPA. In the second phase, the goal was to know the degree of involvement of the clothing workers in the LPA, to characterize the clothing and the businessmen families and to investigate the LPA consequences on both environments. In general, most of the actions proposed by the Action Plan in 2005 was held until 2007. Clothing workers of group A showed higher level of involvement with LPA, with greater awareness of the Plan of Action, and were more present in the arrangement actions as compared to the group B. Most of the industries are micro or small businesses, averaged 15 years, manufacture parts based on the "jeans" and their production is targeted to adult consumers. The participation of clothing workers in LPA improved the clothing business, such as structure and layout of the firms, access to credit, product quality, HR management, finance, employee training, and relationship with the network business and energy efficiency. Businessmen of group A observed greater improvement in their businesses. In the family clothing worker characterization, the sample was predominantly classified as a model nuclear family, with male heads, with 3.7 persons / home, 1.9 children per family and average monthly family income of R$5,450. LPA impact on the families were higher in the group A, and the changes in the domestic production system; stay in the work and family times; family budget arrangement; living with the family; and life consumption and quality were the factors that stood out. The degree of participation of clothing worker in LAP is directly linked to the clothing productive sector and the clothing worker family.